Korelasi Minat Belajar Terhadap Hasil Belajar Peserta Didik Dalam Pembelajaran Fikih Kelas XII MAN 4 Bantul - Ahmad Royhan Anwar; Muhammad Fadli Rahman (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
In general, there are two factors that influence student learning outcomes, namely internal factors and external factors. The interest of students who are assessed on one of these factors has a strong relationship with student learning outcomes. This study examines a problem, namely whether there is a positive relationship between students' interest and learning outcomes in fiqh class XII MAN 4 Bantul. The purpose of this study was to determine the relationship between interest and student learning outcomes in the fiqh class XII MAN 4 Bantul subject. The approach used in this study is quantitative with the type of research that is correlational. This research was conducted at MAN 4 Bantul. All class XII students were taken as the population in this study with a sample of 40 from 4 classes, 10 children were taken from each class. The instrument used was a closed questionnaire using a Likert scale to assess interest in learning, and midterm test scores for science subjects to assess learning outcomes. Product Moment correlation test is used to test the hypothesis of this study. The results of the study stated that there was a positive relationship between students' interest and learning outcomes in fiqh class XII MAN 4 Bantul. This is evidenced from the results of the correlation analysis between students' interest and learning outcomes, a correlation value of 0.79 > 0.361 is obtained, which means that the value of r count is higher than r table. So, the hypothesis in this study can be accepted.